Mercury Identification In Facial Whitening Creams Sold In Cengkareng Market West Jakarta - Apriani Apriani; Steffi Indah (CV. Ridwan Publisher, 2019)
Face whitening creams are cosmetics that are often used by women. Bleach creams contain active ingredients such as hydroquinone and steroids which can provide a whiter skin color while inhibiting pigmentation. This study aims to identify the mercury content in several whitening cream cosmetics circulating in the Cengkareng market in West Jakarta. The research will be carried out qualitatively the mercury color test using the color change method using KI reagent. Based on the results of the research conducted, it can be concluded that the analyst qualitatively, from 25 samples of whitening cream, there were 14 (56%) samples of face whitening cream containing mercury and 11 (44%) samples of face whitening cream that did not contain mercury. Still the presence of facial whitening creams that contain mercury, provides useful information for the public to be more careful in choosing cosmetics. Keywaords: face whitening cream, mercury, mercury color test